The Relationship of Chilean Minors with Brands and Influencers on Social Networks - Feijoo, Beatriz; Sádaba, Charo (MDPI, 2021)
This article presents the results of a study that sought to analyze the relationship between minors and brands on social media. The frequency with which minors search for or share information or subscribe to brand web pages was measured, as well as their following of influencers, who commonly refer to consumer goods. The main purpose of this article is to contribute to learning about the commercial environment that surrounds children in their routines on social media, particularly because of their growing influence in home purchasing decisions. The results, obtained from a survey applied in 501 homes in the Metropolitan Area of Santiago de Chile to minors between 10 and 14 years old, show that the respondents effectively interact with brands through social media. Although it is not a widespread practice among 10- to 12-year-olds, it is increasingly becoming present among 13- to 14-year-olds. Children seem most interested in sportswear, fashion, and technology brands, areas in which children have significant influence in family purchasing decision. Following influencers through social media is also a common activity among minors. In particular, the age groups here studied preferred to follow celebrities, particularly from the worlds of music, football, or YouTube, over specific brands.
Keywords: children; brands; social networks; consumer; influencers; commercial content